Active Ni/SiO2 catalysts with high Ni content for benzene hydrogenation and CO methanation - Le, Thien An; Kang, Jong Kyu; Park, Eun Duck (Applied Catalysis A: General, 2019)
Ni/SiO2 catalysts with high Ni content were prepared from aqueous Ni(NO3)2 solutions by the precipitation method using Na2SiO3 as a silica precursor and precipitant. This is a simple but efficient method to prepare well-dispersed NiO on silica, which can be further transformed to Ni/SiO2 through an additional reduction process. Various techniques such as nitrogen physisorption, X-ray diffraction (XRD), temperature-programmed reduction with hydrogen (H2-TPR), hydrogen chemisorption, high-resolution transmission electron microscopy (HRTEM), X-ray photoelectron spectroscopy (XPS), and inductively coupled plasma-atomic emission spectroscopy (ICP-AES) were employed to characterize the catalysts. The prepared catalysts were applied to two model reactions, benzene hydrogenation and CO methanation. The catalyst showed significantly enhanced performance for these reactions compared to core-shell Ni@SiO2 catalysts and conventional Ni/SiO2 catalysts prepared by wet impregnation.
Keywords: Benzene hydrogenation; Catalyst preparation; Co methanation; Na2SiO3; Ni/SiO2; Benzene Hydrogenation; Catalyst preparation; CO methanation; Hydrogenation; Na2SiO3; Ni/SiO2